Differences in hormone levels around parturition in Hanwoo cattle (Bos taurus coreanae) following artificial insemination and embryo transfer. Issue 3 (22nd February 2022) - Yi, Junkoo; Yum, Soo‐Young; Kim, Daehyun; Han, Sera; Ha, Jaejung; Kim, Jisu; Jung, Daejin; Jang, Goo; Lee, Wonyou; Moon, Joonho
Abstract: Background: With unique genetic traits, Hanwoo cattle ( Bos taurus coreanae ) are well‐adapted to the Korean environment. However, their perinatal mortality rate is 2%–3%, which imposes an economic burden. Objective: Due to insufficient data on hormonal changes around parturition, the timing of parturition is often predicted subjectively; few studies have examined hormones in Hanwoo cattle. We measured the changes in various hormones around parturition, to seek an objective predictor of parturition time. Methods: In 14 female Hanwoo cattle, we measured progesterone, prolactin and cortisol concentrations daily in jugular vein blood samples, beginning 6 days before parturition until 7 days after parturition. Conception was induced in five animals using artificial insemination. Nine animals received embryo transfer. Results: During parturition, the concentration of progesterone decreased significantly in the embryo transfer group ( n = 9) and in the total population ( n = 14); it did not change significantly in the artificial insemination group ( n = 5). Prolactin concentration increased on the day of parturition but did not differ significantly among the groups. Cortisol remained constant throughout the study course. Conclusion: We concluded that parturition time can be predicted in Hanwoo cattle using progesterone concentration. This knowledge can reduce perinatal mortality, which would help to improve farm income and animal welfare.